Marshall Aid - Duncan, G. A. (Statistical and Social Inquiry Society of Ireland, 1950)
The peg on which these reflections are hung is the Economic Cooperation Act of the Congress of the United States of America. That Act was a gesture of magnificent generosity on the part of the American people, equalled only, if at all, by Swedish public and private relief of the victims of the late war. Much of what I have to say will appear critical, directly or by implication, of the forms which that American generosity had to assume, but that is not looking a gift-horse in the mouth. I am considering rather the bit and bridle which the timid pride of the recipients caused to be placed on the American horse.
Read before the Society, 31 March 1950
Keywords: Marshall Aid; Financial Aid; World War II; 314.15